APPLICATION OF MICROSATELLITE MARKERS IN IDENTIFICATION AND PARENTAGE ASSIGNMENT OF SHEEP - Margawati, ET; Tammen, Tammen; Jones, M; Raadsma, HW (BERITA BIOLOGI, 2002)
The accuracy of the parentage reference is the early step of information needed for genotyping study.Inaccurate data of recording sheep numbers is often occurred. Sometimes, we found sheep or lambs with uncertain original parents. This study was designed to identify the parentages of sheep and to find the putative parents of lambs. Using an advance DNA technology in molecular genetics particularly in genotyping study, those purposes can be clarified. DNA of sheep were isolated from fresh blood samples in EDTA using a high salt method. A concentration of 50ng/(il DNA was used for amplification. Several microsatellite markers were applied in the amplification. Using a DNA analyser and sequencer, PCR products were analysed to look at the figures of alleles (bands). Results showed that using microsatellite markers could inform that parents of several experimental lambs were incorrect. It was found that putative parents of some lambs were generated from incorrect parents. This study suggests that microsatellite marker can be used to clarify unknown original parents.